Glacier meltwater has limited contributions to the total runoff in the major rivers draining the Tibetan Plateau - Yi Nan; Fuqiang Tian; Jeffrey McDonnell; Guangheng Ni; Lide Tian; Zongxing Li; Denghua Yan; Xinghui Xia; Ting Wang; Songjun Han; Kunbiao Li (npj Climate and Atmospheric Science)
Abstract The Tibetan Plateau is the headwaters of several major river basins, but uncertainties exist in the estimated contributions of glacial melt and groundwater to runoff. We present a new tracer-aided glacio-hydrological model constrained by multiple datasets for five major river basins of the Tibetan Plateau. We show that the contribution of glacier melt to the annual runoff is less than 5% in all the five basins at the outlets—much less than previous estimates. Our secondary finding is that the partitioning between surface runoff and groundwater flow varied greatly across the watersheds, with groundwater runoff contributing 35–75% of the annual runoff. The contribution of glacier melt has a strong spatial variability and scale dependency, but the population heavily dependent on it is limited, so a potential significant decrease in water resources due to glacier shrinkage is not a problem that should raise public worries in the Tibetan Plateau.